Penggunaan Media Audiovisual dan Flipchart terhadap Pengetahuan Kesehatan Gigi dan Mulut pada Anak Sekolah Dasar - Widyastuti, Nugraheni; Tri Safitri, Mutiara; Nur Aida, Wanda; Sainuddin; Adlinah Fatman, Siti (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
requiring promotional efforts through effective educational media. To improve children's understanding, effective, engaging learning media are needed, and they are appropriate to their cognitive characteristics. One such medium is audiovisual materials and flipcharts.This study aims to determine the effectiveness of audio-visual media and flipcharts in improving oral and dental health knowledge in elementary school students. The type of research used is quantitative with a Two Group Pretest-Posttest Design experiment on 88 respondents of fifth-grade students of Perumnas Elementary School, Makassar City, who were divided into two treatment groups of 44 students each. The research instrument was a questionnaire on oral and dental health knowledge given before and after counseling. The results showed a significant increase in knowledge in both groups with the Wilcoxon test (p = 0.000 <0.05). The average knowledge of students who were given counseling through audio-visual media increased from 56.93 to 81.02 with a difference of 29.09, while the flipchart group increased from 47.61 to 76.25 with a difference of 28.67. The conclusion of this study is that both media are proven to be effective in increasing knowledge of dental and oral health of elementary school students, but audio-visual media is more effective than flipcharts because it is able to attract students' attention through a combination of sound and moving images that make it easier to understand the information.  Keywords: Audiovisual; flipchart; knowledge; dental health; elementary school children